A web-page-based software program for technology enhanced learning (TEL) of combinatorial logic circuits - Tan, Wei Heng (Nanyang Technological University, 2024)
This project endeavours to establish a Technological-Enhanced Learning (TEL) platform aimed at facilitating comprehension of Combinatorial Logic Circuits, which are pivotal components in digital electronics for grasping the fundamentals of digital systems. Traditionally introduced in the first year of Electrical and Electronic Engineering curriculum, this web-based software offers an interactive learning environment focussing on Logical Functions to assist students in their academic journey while encouraging the practical application of acquired knowledge.